STYLISTIC DEVICES IN ENGLISH LITERARY TEXTS AND THEIR FUNCTIONS - Abdulhamidova Gulzoda,; G'ofurova S. M., (TADQIQOTLAR, 2026)
Annotation:  This  article  explores  the  various  stylistic  devices  employed  in English literary texts and their multifaceted functions. By analyzing examples from different  genres,  it  aims  to  elucidate  how  these  devices  enhance  meaning,  evoke emotions, and contribute to the overall aesthetic experience of literature.